Comparative Analysis of Flipped Classroom Implementation in Western and Indian Indoctrination (American Journal of Arts and Human Science, 2024)
The flipped classroom, a popular teaching method in Western countries, has gained popularity due to its ability to address traditional teaching limitations. However, India’s diverse education system presents unique challenges, including technological disparities, traditional practices, and curriculum rigidity. This study aimed to compare the implementation and outcomes of the flipped classroom model in Western countries and India, revealing key factors contributing to its success or challenges. The study aimed to provide insights into how the flipped classroom model can be adapted and optimized to fit different educational environments, ultimately improving learning outcomes and teaching practices globally. The study has explored adopting and implementing the flipped classroom model in Western countries and India, identifying challenges and barriers. It has also evaluated educational outcomes, explored the role of technological infrastructure, assesses teacher readiness and training, and provides explored the role of technological infrastructure, assessed teacher readiness and training, and explored the role of technological infrastructure, assessed teacher readiness and training, and provided recommendations for enhancing its effectiveness in India. The flipped classroom model can enhance educational outcomes by increasing engagement and active learning. However, India faces unique challenges and needs targeted solutions. India should invest in technology, professional development, curriculum adaptation, and community engagement to maximize its benefits.